Developing a Reference Framework for Typical Development in the Young Pig. (7th June 2021) - Vu, Vinh; Dilger, Ryan; Donovan, Sharon M.; Li, Qian; Gross, Gabriele; Brink, Lauren; Fleming, Stephen
Abstract: Objectives: The majority of infants in the US do not receive exclusive breastfeeding in the first six months of age, highlighting the necessity of infant formula. The artificially reared piglet is a common model utilized to support substantiation of novel bioactive components in milk or infant formula. However, it is currently unclear to what extent maternal and environmental rearing confounders affect growth outcomes in early life nutrition piglet studies. The objective of the present work is to use historical data to begin to chart typical development of the pig and to develop healthy reference value ranges for the purpose of assessing the safety of bioactive components in infant formula. Methods: 8 piglet studies conducted at the University of Illinois Urbana-Champaign over the past ten years were compiled to create and model reference values for body and organ weights in artificially-reared and sow reared pigs. Metadata were organized to include milk replacer sources, bioactive components, sex, breed, source of herd, feeding rates, rearing styles, and health status. A combination of statistical models including simple linear regression, polynomial regression, and generalized additive models were used to analyze how such parameters influence typical growth. The diet of the 18 studies were blinded during data modeling phase. Results: Over 13, 000 data points from over 500 animals were identified to be suitable for data mining. Minimal differences in the growth of artificially or sow reared pigs were observed in the first 30 days of life ( P > 0.05). Similarly, male and female bodyweight growth were nearly identical ( P > 0.05). Development outcomes such as brain, liver, and intestinal organ weights were classified as typical for developing pigs. A subset of the data containing subjects with poor growth was identified to model growth under deficient or sub-optimal conditions. Conclusions: The use of artificial rearing had no impact on body weight, nor did sex contribute to differences in growth during early life. Ultimately, these data can be used to create preliminary weight-for-age charts in the pig model to better interpret whether bioactive ingredients tested in the pig model affect animal growth within typical reference values. Funding Sources: Funding was provided by Mead Johnson Nutrition, LLC, a Reckitt Benckiser LLC company.